2016
DOI: 10.7717/peerj.1966
|View full text |Cite
|
Sign up to set email alerts
|

Testing the potential of a ribosomal 16S marker for DNA metabarcoding of insects

Abstract: Cytochrome c oxidase I (COI) is a powerful marker for DNA barcoding of animals, with good taxonomic resolution and a large reference database. However, when used for DNA metabarcoding, estimation of taxa abundances and species detection are limited due to primer bias caused by highly variable primer binding sites across the COI gene. Therefore, we explored the ability of the 16S ribosomal DNA gene as an alternative metabarcoding marker for species level assessments. Ten bulk samples, each containing equal amou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 35 publications
3
99
0
Order By: Relevance
“…For DNA metabarcoding, we used two different primer sets targeting two mitochondrial DNA (mtDNA) genes commonly used in arthropod studies: cytochrome c oxidase subunit I (COI) (~211 bp fragment) (Zeale, Butlin, Barker, Lees, & Jones, 2011) and 16S ribosomal RNA (~160 bp fragment) (Elbrecht et al, 2016) (Supporting Information Figure S1). Primers were uniquely tagged.…”
Section: Pcr Amplificationmentioning
confidence: 99%
See 2 more Smart Citations
“…For DNA metabarcoding, we used two different primer sets targeting two mitochondrial DNA (mtDNA) genes commonly used in arthropod studies: cytochrome c oxidase subunit I (COI) (~211 bp fragment) (Zeale, Butlin, Barker, Lees, & Jones, 2011) and 16S ribosomal RNA (~160 bp fragment) (Elbrecht et al, 2016) (Supporting Information Figure S1). Primers were uniquely tagged.…”
Section: Pcr Amplificationmentioning
confidence: 99%
“…The generic primers used in this study have been designed for metabarcoding of degraded DNA, and tested previously (Elbrecht et al, 2016;Zeale et al, 2011). Given the short amplicon size, they perform comparatively well by resolving most taxa to species level (Tables S2-S3).…”
Section: Choice Of Primers and Database Coverage In Metabarcoding Smentioning
confidence: 99%
See 1 more Smart Citation
“…Using multiple primer pairs is expected to reduce amplification biases and increase the opportunities of detecting all targeted taxonomic groups. To fully understand the performance of a multigene metabarcoding approach, mock communities are ideal because the expected number of species is known a priori (Clarke, Soubrier, Weyrich, Weyrich, & Cooper, 2014;Elbrecht et al, 2016;Kermarrec et al, 2013). Nonetheless, there are few studies that have taken this approach (but see Clarke et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, by using barcoding regions with less variability, taxonomic resolution will decrease and therefore it is as mentioned, desirable to attempt to reduce these biases in order to retain the use of COI. Fortunately, a number of recent studies have shown that while COI is variable, with some of the degenerate primers available such as mCOIintF (Leray et al, 2013) and jgHCO2198 (Geller et al, 2013), it is nevertheless possible to get at least for some groups a comparable taxonomic coverage to alternative barcoding regions (Clarke, Beard, Swadling, & Deagle, 2017;Elbrecht et al, 2016). The variation within COI does, however, mean that a large amount of degeneracy is needed.…”
Section: Introductionmentioning
confidence: 99%